FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN DI BEI TAHUN 2014-2019 - Putra Mulia Wiryawidjaya; Endang Masitoh; Purnama Siddi (Jurnal Proaksi, 2021)
ABSTRACT This study aims to determine and analyze the effect of dividend policy (DPR), funding decisions (DER), profitability (ROE), and company size (SIZE) on firm value (PBV) in the automotive sub-sector and components on the Indonesia Stock Exchange 2014-2019. This type of research is quantitative, the research method uses multiple linear regression. The population of this study were 15 manufacturing companies in the automotive and component sub-sector. Sample selection using purposive sampling method, in order to get 5 companies as research samples. The results show that profitability (ROE) affects firm value (PBV), while dividend policy (DPR), funding decisions (DER), and firm size (SIZE) have no effect on PBV firm value. Keywords: DER, DPR, PBV, ROE, SIZE ABSTRACT This study aims to determine and analyze the effect of dividend policy (DPR), funding decisions (DER), profitability (ROE), and company size (SIZE) on firm value (PBV) in the automotive sub-sector and components on the Indonesia Stock Exchange 2014-2019. This type of research is quantitative, the research method uses multiple linear regression. The population of this study were 15 manufacturing companies in the automotive and component sub-sector. Sample selection using purposive sampling method, in order to get 5 companies as research samples. The results show that profitability (ROE) affects firm value (PBV), while dividend policy (DPR), funding decisions (DER), and firm size (SIZE) have no effect on PBV firm value. Keywords: DER, DPR, PBV, ROE, SIZE